First Human In Vivo Neuroelectrophysiology Recordings of Uncrossed Dentatothalamocortical White-Matter Connections: On the Fast Tract. (23rd August 2022) - Brogna, Christian; Perera, Noemia; Ghimire, Prajwal; Bruchhage, Muriel M.K.; Abela, Eugenio; Richardson, Mark P.; Vergani, Francesco; Bhangoo, Ranjeev; Ashkan, Keyoumars
Abstract : Objectives: We aim to demonstrate intraoperative recording of cerebellar to cortical pathways that have not been previously recorded in humans, though imaged. Methods: We report 2 cases with intraoperative neurophysiologic mapping of cerebellocortical tracts. Direct electrical stimulation of subcortical cerebellum along with recordings of cortical evoked potential and motor muscle recordings was performed during surgery. MR tractography data from healthy participants were used to further illustrate the pathways. Results: Neurophysiologic recordings showed large waveforms of evoked potentials in bilateral electrodes over premotor/motor cortices on stimulation of the dentate nucleus. EMG recordings showed responses in face and neck muscles on stimulation of the dentate nucleus at the motor threshold. We thus demonstrated first-in-human in vivo neurophysiologic evidence of cerebellum to cortex responses through an uncrossed dentatothalamocortical tract to the motor/premotor cortices. Discussion: This technique provides a methodology for the direct mapping of the cerebellum and cerebello-cerebral connections. We hypothesize a direct structural connection from the dentate nucleus to the premotor and motor cortices, as well as to ipsilateral hemibody muscles, acting as a fast route of cerebellar output and back up for immediate motor responses. This will further help explain the modulatory effects of the cerebellum on motor, language, and cognitive functions.